Viability of Aboriginal Communities Beyond Mine Closure - Ross, N.; Bond, B. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Historically, the focus of mine closure has been put on environmental aspects without addressing long- lasting social and economic impacts of mine closure on communities. For aboriginal communities in Canada, these impacts can be significant. Provisions for post-closure well-being strategies are increasingly included in Impacts and Benefits Agreements signed between aboriginal communities and mining companies. However, communities are often inadequately prepared and lack the capacity to offset the impacts. The Mining Information Kit for Aboriginal Communities produced by the Government of Canada et al. (2006) was designed to provide basic information on the mining sequence including the last phase, mine closure and reclamation, as well as opportunities that may be available. The kit also provides ideas and examples of how industry, governments and communities can work together to build community capacity to plan in advance, manage opportunities and develop economic alternatives following mine closure.